Aircraft Noise Levels and Their Impact on the Health of Communities Around Tampa Padang Airport, West Sulawesi: A Descriptive Study - Ridhayani Adiningsih; Agus Erwin Ashari; Miftah Chairani; Sachrul Romadhan S (Universitas Mandala Waluya, 2025)
Aircraft noise exposure is a significant environmental health issue for communities living near airports. Although global evidence shows a link between aircraft noise and health impacts, research on regional airports in Indonesia is still very limited. This study fills that gap by investigating noise exposure levels and health impacts at Tampa Padang Airport, Mamuju, West Sulawesi. A descriptive mixed-methods approach was conducted in Bebanga Village in January 2025. Noise measurements were taken at three strategic locations (500m, 750m, and 1000m from the runway) using a Sound Level Meter calibrated according to the SNI 7231:2009 standard. Health impact data were collected from 94 respondents through validated structured interviews. Aircraft noise levels ranged from 64.5 to 92.1 dB, exceeding the residential zone quality standard of 55 dB (Indonesian regulation) and WHO guidelines (45 dB Lden). The landing phase produced higher noise levels (74.7-92.1 dB) than the take-off phase (64.5-83.1 dB). Health assessments showed that 16% of respondents experienced mild hearing impairment and 1.1% experienced moderate impairment. No sleep disturbance or psychological stress was found. Although noise exposure exceeded national and international standards, the current health impact is relatively limited, possibly due to habituation and the absence of night flights. However, long-term monitoring and implementation of noise mitigation strategies are still necessary.